2002
DOI: 10.1128/jvi.76.7.3329-3337.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Vaccinia Virus-Induced T-Cell Immunity: Quantitation of the Response to the Virus Vector and the Foreign Epitope

Abstract: Recombinant vaccinia viruses (rVV) have been extensively used as vaccines, but there is little information about the total magnitude of the VV-specific T-cell response and how this compares to the immune response to the foreign gene(s) expressed by the rVV. To address this issue, we quantitated the T-cell responses to both the viral vector and the insert following the infection of mice with VV expressing a cytotoxic T lymphocyte (CTL) epitope (NP118-126) from lymphocytic choriomeningitis virus (LCMV). The LCMV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(191 citation statements)
references
References 22 publications
10
178
3
Order By: Relevance
“…CD8 ϩ T cells from VV-infected BALB/c mice (H-2 d haplotype) recognized VV-infected targets and produced IFN-␥ (Fig. 1A) (25). In contrast, Ͻ1% of VV-induced CD8 ϩ T cells responded to CPV-infected targets.…”
Section: Cpv and Vv-specific Ctl Are Stimulated By Target Cells Infecmentioning
confidence: 96%
See 1 more Smart Citation
“…CD8 ϩ T cells from VV-infected BALB/c mice (H-2 d haplotype) recognized VV-infected targets and produced IFN-␥ (Fig. 1A) (25). In contrast, Ͻ1% of VV-induced CD8 ϩ T cells responded to CPV-infected targets.…”
Section: Cpv and Vv-specific Ctl Are Stimulated By Target Cells Infecmentioning
confidence: 96%
“…with 2 ϫ 10 6 PFU of VV or CPV. Spleens were collected on day 8 postinfection for analysis of antiviral T cell responses as described (25), and 10 6 splenocytes were mixed with 5 ϫ 10 5 A20 or MC57 cells that were uninfected or infected overnight. After 6 h of incubation with the target cells in the presence of BFA, cells were stained for CD8 and then fixed, permeabilized, and stained intracellularly for IFN-␥ and TNF-␣.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…3C was performed using splenocytes obtained 2 weeks after vaccination with VV-COP. We also assessed by ICCS whether the peptide-specific CD8 ϩ T cells are maintained as memory T cells, by examining the T-cell response on day 28 postvaccination, since it has been shown that the CD8 ϩ T-cell response detected at day 30 is maintained at the same level for Ͼ300 days (18). As shown in Fig.…”
Section: Vol 82 2008 Vaccination With A27l B5r and D8l Proteins 3521mentioning
confidence: 99%
“…The latter, however, introduces the problem of immunity against viral proteins which may be pre-existing and can block any boosting [15]. There is the additional possibility of competition from viral epitopes which can suppress anti-tumor responses in patients [16]. We found that priming with DNA followed by boosting with DNA plus electroporation gives a dramatic boost of immunity.…”
Section: Delivery Of Antigenmentioning
confidence: 82%